Progression of Mitral Regurgitation in Rheumatic Valve Disease: Role of Left Atrial Remodeling - Gomes, Nayana F. A.; Silva, Vicente Rezende; Levine, Robert A.; Esteves, William A. M.; de Castro, Marildes Luiza; Passos, Livia S. A.; Dal-Bianco, Jacob P.; Pantaleão, Alexandre Negrão; da Silva, Jose Luiz Padilha; Tan, Timothy C.; Dutra, Walderez O.; Aikawa, Elena; et al. (Frontiers in Cardiovascular Medicine, 2022)
Mitral regurgitation (MR) is the most common valve abnormality in rheumatic heart disease (RHD) often associated with stenosis. Although the mechanism by which MR develops in RHD is primary, longstanding volume overload with left atrial (LA) remodeling may trigger the development of secondary MR, which can impact on overall progression of MR. This study aims to assess the incidence and predictors of MR progression in patients with RHD. METHODS: RHD patients with non-severe MR associated with any degree of mitral stenosis were selected. The primary endpoint was progression of MR, which was defined as an increase of one grade in MR severity from baseline to the last follow-up echocardiogram. Risk of MR progression was estimated accounting for competing risks. RESULTS: 539 patients, (46.2 ± 12 years and 83% of women). At follow-up time of 4.2 years (IQR: 1.2 to 6.9 years), 54 patients (10%) displayed MR progression with an overall incidence of 2.4 per 100 patient-years. Predictors of MR progression by the Cox model were age (adjusted hazard ratio [HR] 1.541, 95% CI 1.222 - 1.944), and LA volume (HR 1.137, 95% CI 1.054 - 1.226). By considering competing risk analysis, the direction of the association was similar for the rate (Cox) and incidence (Fine-Gray model) of MR progression. CONCLUSIONS: In RHD patients with a full spectrum of MR severity, progression of MR occurs over time predicted by age and LA volume. Left atrial enlargement may play a role in the link between primary and secondary MR in RHD patients